Effectiveness of purple led for inactivation of Bacillus subtilis and Escherichia coli bacteria in in vitro sterilizers - A. K. Yaqubi; S. D. Astuti; P.A.D. Permatasari; N. Komariyah; E. Endarko; A. H. Zaidan (Biomedical Photonics, 2023)
Bacteria are inactivated using a technique called photodynamic inactivation, which combines light with a photosensitizer with the right spectrum. The objective of this study is to ascertain the eciency of purple LEDs for photoinactivating Bacillus subtilis and Escherichia coli bacteria as well as the ideal purple LED exposure energy density. This study technique involves exposing bacteria to purple LED radiation. Two elements of variation are used during irradiation. The first variation is the illumination variation at distances of 3 cm, 6 cm, 9 cm, and 12 cm. The second variation involves changing the amount of radiation for 30, 60, 90, and 120 minutes. The Total Plate Count (TPC) method was used to count the number of colonies. Statistical tests were utilized in data analysis, namely the One Way Anova test (analysis of variance). The results of this study indicated that 395 nm purple LED irradiation caused a decrease in Log CFU/mL of Bacillus subtilis and Escherichia coli bacteria. Inactivation of Bacillus subtilis bacteria showed a higher mortality percentage than Escherichia coli bacteria. Changes in other irradiation distances also showed a higher percentage of death for Bacillus subtilis bacteria than Escherichia coli bacteria. The highest percentage of death was 98.5% for Bacillus subtilis bacteria and 94.3% for Escherichia coli bacteria at position C with an irradiation distance of 3 cm and an energy density of 524 J/cm2 with an LED exposure time of 120 minutes. This shows that the percentage of death of bacteria Bacillus subtilis and Escherichia coli increased with increasing doses of LED energy with the greatest percentage of death in Gram-positive bacteria Bacillus subtilis.